2020
DOI: 10.1038/s41467-019-13906-8
|View full text |Cite
|
Sign up to set email alerts
|

The proteasome 19S cap and its ubiquitin receptors provide a versatile recognition platform for substrates

Abstract: Proteins are targeted to the proteasome by the attachment of ubiquitin chains, which are markedly varied in structure. Three proteasome subunits-Rpn10, Rpn13, and Rpn1-can recognize ubiquitin chains. Here we report that proteins with single chains of K48-linked ubiquitin are targeted for degradation almost exclusively through binding to Rpn10. Rpn1 can act as a co-receptor with Rpn10 for K63 chains and for certain other chain types. Differences in targeting do not correlate with chain affinity to receptors. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
99
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(107 citation statements)
references
References 97 publications
6
99
0
2
Order By: Relevance
“…Lys-48-linked poly-ubiquitin is the major signal of numerous short-lived proteins and unfolded proteins for proteasomal degradation [ 72 ]. Lys-11-linked poly-ubiquitin is also involved in degradation of short-lived cell cycle proteins and in the ERAD (endoplasmic reticulum-associated degradation) pathway upon ER stress [ 73 ]. Furthermore, small aggregated proteins are selectively degraded via the autophagy–lysosome system.…”
Section: Ubiquitination In Protein Degradationmentioning
confidence: 99%
“…Lys-48-linked poly-ubiquitin is the major signal of numerous short-lived proteins and unfolded proteins for proteasomal degradation [ 72 ]. Lys-11-linked poly-ubiquitin is also involved in degradation of short-lived cell cycle proteins and in the ERAD (endoplasmic reticulum-associated degradation) pathway upon ER stress [ 73 ]. Furthermore, small aggregated proteins are selectively degraded via the autophagy–lysosome system.…”
Section: Ubiquitination In Protein Degradationmentioning
confidence: 99%
“…Protein expression and purification. Mammalian proteasomes were purified from Psmd14 Flag/Flag mouse embryonic fibroblasts (Rpn11-Flag MEFs) by anti-Flag immunoaffinity chromatography essentially as described previously 29,36 . Rpn11-Flag MEFs were lysed with ice-cold buffer B (20 mM Tris-HCl [pH 7.4], 0.2% [v/v] NP-40, 150 mM NaCl, 1 mM dithiothreitol [DTT], 2 mM ATP, and 5 mM MgCl 2 ), clarified by centrifugation (20,000 × g for 10 min at 4°C), immunoprecipitated using anti-Flag M2 agarose affinity beads (Sigma #A2220).…”
Section: Methodsmentioning
confidence: 99%
“…In yeast, branched K29/48 chains formed by Ufd4 and Ufd2 in the context of the UFD pathway bind more tightly than homotypic K29-linked chains to Rpn10 and the proteasome shuttling factors Rad23 and Dsk2 13 . Interestingly, although K11-linked chains were initially thought to act as prominent degradation signals, recent work has shown that unbranched K11 chains bind only weakly to proteasomes and do not support the degradation of model substrates by proteasomes in vitro 49 , 50 . Together, these findings support the idea that branched chains are generally more potent degradation signals than their unbranched counterparts.…”
Section: Physiological Functions Of Branched Ubiquitin Chainsmentioning
confidence: 99%